Fredholm and Volterra Integral Equations - Dr. Raga Hassan Ali Shiekh (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
We will focus on Fredholm and Volterra integral equations. We have examined the development of integral equations that has significant applicability in physical problems. A multitude of initial and boundary value issues can be converted into integral equations. Mathematical physics problems are typically regulated by integral equations. There are several categories of integral equations. Singular integral equations are highly beneficial in numerous physical issues, including elasticity, fluid mechanics, and electromagnetic theory.